ENVIRONMENTAL INFLUENCES ON CHILDREN’S PHYSICAL ACTIVITY AND DIETS IN RURAL OREGON: RESULTS OF A YOUTH PHOTOVOICE PROJECT - Findholt, Nancy E. (Online J Rural Nurs Health Care, 2010)
Little is known about the effect of the rural environment on children’s physical activity and food choices. In this study, six rural adolescents participated in a photovoice assessment to document conditions that influenced children’s activity and diets. Physical activity was hindered by inadequate recreational resources, unsafe streets, and distance, but was promoted by the natural environment and support for youth sports. Healthy eating was hindered by busy lifestyles, limited access to healthy foods, access to and promotion of unhealthy foods, and social values, but was promoted by the agricultural setting and gardening. While many of these factors occur in non-rural settings, the findings suggest that rural communities have unique strengths and barriers that must be considered when developing interventions.